Comparison of Orthodontic Medicaid Funding in the United States 2006 to 2015 - Minick, Gerald; Tilliss, Terri; Shellhart, W. Craig; Newman, Sheldon M.; Carey, Clifton M.; Horne, Andrew; Whitt, Susan; Oesterle, Larry J. (Frontiers in Public Health, 2017)
Introduction Orthodontic treatment is reimbursed by Medicaid based on orthodontic and financial need with qualifiers determined by individual states. Changes in Medicaid-funded orthodontic treatment following the “Great Recession” in 2007 and the enactment of the Affordable Care Act in 2010 were compared for the 50 United States and the District of Columbia to better understand disparities in access to care. The results from this 2015 survey were compared to data gathered in 2006 (1). Materials and methods Medicaid officials were contacted by email, telephone, or postal mail regarding the age limit for treatment, practitioner type who can determine eligibility and provide treatment, records required for case review, and rate and frequency of reimbursement. When not attained by direct contact, the information was gleaned from online websites, provider manuals, and state orthodontists. Results Information gathered from 50 states and the District of Columbia documents that Medicaid program characteristics and expenditures continue to vary by state. Expenditures and reimbursement rates have decreased since 2006 and vary widely by geographic region. Some states have tightened restrictions on qualifiers and increased submission requirements by providers. Conclusion The variation and lack of uniformity that still exists among Medicaid orthodontic programs in different states creates disparities in orthodontic care for US citizens. Barriers to care for Medicaid-funded orthodontic treatment have increased since 2006.